2023
DOI: 10.1101/2023.01.23.525284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RIPK3 promotes brain region-specific interferon signaling and restriction of tick-borne flavivirus infection

Abstract: Innate immune signaling in the central nervous system (CNS) exhibits many remarkable specializations that vary across cell types and CNS regions. In the setting of neuroinvasive flavivirus infection, neurons employ the immunologic kinase receptor-interacting kinase 3 (RIPK3) to promote an antiviral transcriptional program, independently of the traditional function of this enzyme in promoting necroptotic cell death. However, while recent work has established roles for neuronal RIPK3 signaling in controlling mos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 56 publications
(74 reference statements)
2
9
0
Order By: Relevance
“…Notably, Ripk3 -/neurons exhibited hundreds of differentially expressed genes (DEGs) compared to Ripk3 +/+ controls following infection with both viruses (Figure 1D-E). Gene ontology (GO) enrichment analysis of significant DEGs revealed overrepresentation of terms related to immune activation, especially immune cell chemotaxis, when comparing Ripk3 -/neurons to Ripk3 +/+ controls in both infection groups (Figure 1F-G), consistent with our previous work demonstrating a central for RIPK3 in promoting expression of chemokines and other innate immune genes in neurons during flavivirus infection [13][14][15] . To our surprise, however, these comparisons also revealed enrichment of GO terms associated with neurologic functions, including terms related to neurotransmission such as synaptic signaling, long-term potentiation, and neurotransmitter release (Figure 1H-I).…”
Section: Ripk3 Is a Key Regulator Of Neurologic Gene Expression Durin...supporting
confidence: 90%
See 2 more Smart Citations
“…Notably, Ripk3 -/neurons exhibited hundreds of differentially expressed genes (DEGs) compared to Ripk3 +/+ controls following infection with both viruses (Figure 1D-E). Gene ontology (GO) enrichment analysis of significant DEGs revealed overrepresentation of terms related to immune activation, especially immune cell chemotaxis, when comparing Ripk3 -/neurons to Ripk3 +/+ controls in both infection groups (Figure 1F-G), consistent with our previous work demonstrating a central for RIPK3 in promoting expression of chemokines and other innate immune genes in neurons during flavivirus infection [13][14][15] . To our surprise, however, these comparisons also revealed enrichment of GO terms associated with neurologic functions, including terms related to neurotransmission such as synaptic signaling, long-term potentiation, and neurotransmitter release (Figure 1H-I).…”
Section: Ripk3 Is a Key Regulator Of Neurologic Gene Expression Durin...supporting
confidence: 90%
“…Extensive previous work has shown that neurons are resistant to programmed cell death 65 , including RIPK3-mediated necroptosis 10 . We and others have shown that the cell-death independent functions of RIPK3 are critical for host control of CNS viral infection through the well-established functions of this kinase in promoting immunological gene expression [13][14][15] . Here, our findings underscore an even more extensive role for RIPK3 in controlling neuronal biology during infection, including unexpected functions in regulating excitatory neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that ISGs play critical roles to restrict ZIKV replication 27–33 . For example, Viperin has been reported to inhibit ZIKV RNA translation by activating ribosome collision‐dependent pathway 27 .…”
Section: Discussionmentioning
confidence: 99%
“…25 Many studies have reported that ISGs play critical roles to restrict ZIKV replication. [27][28][29][30][31][32][33] For example, Viperin has been reported…”
Section: Discussionmentioning
confidence: 99%